1980
DOI: 10.1002/pol.1980.170180105
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of acetylene and its monosubstitutes in the presence of halides and oxohalides of molybdenum and tungsten

Abstract: MoCl5, WCl6, and OMoCl4 were found to be effective initiators for the polymerization of acetylene and its monosubstituted derivatives RCCH. The polymerization proceeded in homogeneous and heterogeneous media and was carried out in nonpolar (chloroalkanes, aromatic hydrocarbons) and polar (THF, acetone, dioxane, carboxylic acids) solvents to give a high yield of polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…[7][8][9] It is known that the interesting features of silicon containing polymers are high thermal stability, gas permeabilities, weather resistance, insulating properties, and so on. 10,11 Recently, many studies have been reported that polymers containing trimethylsilyl derivatives has excellent gas permeability. [12][13][14][15][16][17] Soluble polyimides containing bulky and flexible trimethylsilyl offer particular promise in gas separation membrane application due to their superior mechanical property, high permeability and permselectivity.…”
mentioning
confidence: 99%
“…[7][8][9] It is known that the interesting features of silicon containing polymers are high thermal stability, gas permeabilities, weather resistance, insulating properties, and so on. 10,11 Recently, many studies have been reported that polymers containing trimethylsilyl derivatives has excellent gas permeability. [12][13][14][15][16][17] Soluble polyimides containing bulky and flexible trimethylsilyl offer particular promise in gas separation membrane application due to their superior mechanical property, high permeability and permselectivity.…”
mentioning
confidence: 99%
“…Sharp ~3C signals at 34.2 and 129.9 ppm were assigned to small amounts of trimer. The broad signal of the vinylic region clearly indicates atactic microstructures for all polymers [17,18]. Fr-IR spectroscopy (KBr pellets) proved the absence of carbonylic impurities (1705 cm -1) [17].…”
Section: Resultsmentioning
confidence: 88%
“…The broad signal of the vinylic region clearly indicates atactic microstructures for all polymers [17,18]. Fr-IR spectroscopy (KBr pellets) proved the absence of carbonylic impurities (1705 cm -1) [17]. The highest yieldwas realized in the case of the unsubstituted o-silylated but-3-yn-l-ol, la.…”
Section: Resultsmentioning
confidence: 89%
“…The substituted poly(acetylene)s are practically more useful because of their higher stability towards air and their solubility in organic solvents compared to non-substituted poly(acetylene) [9][10][11][12]. The polymerization of substituted alkynes has been carried out with a number ill-defined Mo-, W-, Ru-, Rh-etc.…”
Section: Introductionmentioning
confidence: 99%